Digital transformation of Higher Education: what's next? - Dinusha Weerawardane (University of West London, 2021)
The Covid-19 pandemic has exponentially accelerated digital transformation within the higher education sector, and has given us the opportunity to re-think and re-shape how we do things. This article explores what true digital transformation looks like, where it could potentially lead us and what universities of the future might look like.